2018
DOI: 10.1039/c7cc08588e
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal free regio-selective C–H hydroxylation of chromanones towards the synthesis of hydroxyl-chromanones using PhI(OAc)2 as the oxidant

Abstract: The chromanone scaffold is considered as a privileged structure in drug discovery. Herein, we report a highly efficient PhI(OAc) mediated regioselective, direct C-H hydroxylation of chromanones. This method offers easy access to substituted 6-hydroxy chromanones in moderate to good isolated yields, thus paving the way for their pharmaceutical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…21 Salicylate 25 was prepared by the Pinnick oxidation of 24 22 and Fischer esterification in 81% yield. Under Muthukrishnan's conditions, 23 (diacetoxyiodo)benzene (PIDA) in trifluoroacetic acid (TFA), the oxidative nucleophilic substitution reaction proceeded selectively at the C3 position (27/28 = 2:1). Finally, we found that the use of a TFA/AcOH mixed solvent improved the selectivity to give 27 (27/28 = 7:1), which underwent a one-pot hydrolysis to form 26 in 68% yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21 Salicylate 25 was prepared by the Pinnick oxidation of 24 22 and Fischer esterification in 81% yield. Under Muthukrishnan's conditions, 23 (diacetoxyiodo)benzene (PIDA) in trifluoroacetic acid (TFA), the oxidative nucleophilic substitution reaction proceeded selectively at the C3 position (27/28 = 2:1). Finally, we found that the use of a TFA/AcOH mixed solvent improved the selectivity to give 27 (27/28 = 7:1), which underwent a one-pot hydrolysis to form 26 in 68% yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The alternative synthesis [38] was initiated with commercial 2-chloro-1,4-dimethoxybenzene, which was converted to methyl 4-chloro-2,5-dimethoxybenzoate 42 by three-step sequence (formylation, Pinnick oxidation, and acidic esterification). The oxidative nucleophilic substitution reaction [39,40] using PIDA in trifluoroacetic acid (TFA)/AcOH mixed solvent occurred selectively at the C3 position (C3/C6 = 6:1) to give 43, which was directly subjected to basic hydrolysis to produce phenol 39 in 68% yield. The asymmetric synthesis of (R)-4 is essential for the total synthesis of the natural products in the chloropupukeananin family.…”
Section: Pestheic Acid and Maldoxinmentioning
confidence: 99%
“…Figure S1). In addition, a minor overoxidized product (<5%) was detected . Encouraged by these initial results, a number of reaction parameters (e.g., solvent, oxidant, temperature, and necessity of the palladium catalyst) were examined.…”
mentioning
confidence: 99%
“…In addition, a minor overoxidized product (<5%) was detected. 18 Encouraged by these initial results, a number of reaction parameters (e.g., solvent, oxidant, temperature, and necessity of the palladium catalyst) were examined. The reaction proceeded at room temperature, although additional time was needed to achieve similar product yield (entry 2).…”
mentioning
confidence: 99%